Purchase Unwillingness and Willingness of Indonesian Consumers towards Israeli Products - Suhud, Usep (Binus Business Review, 2017)
This research aimed to measure factors influencing purchase willingness and purchase unwillingness on Israeli products. Four predictor variables including consumer animosity, product judgment, boycott participation, and boycott motivation were used. Data were collected by an online survey, and it attracted 337 participants. Three stages of data analysis were applied, those were exploratory analyses, confirmatory factor analyses, and Structural Equation Model (SEM). In total, there were seven hypotheses tested. This research finds a significant impact of animosity on product judgment, boycott participation, and boycott motivation. Furthermore, product judgment and boycott participation significantly affect purchase willingness. Meanwhile, boycott participation and boycott motivation significantly affect purchase unwillingness.